Ventilator associated pneumonia - Sham Lohiya; Sachin Damke; J Vagha; Kundan Mittal (Wolters Kluwer Medknow Publications, 2019)
Ventilator-associated pneumonia (VAP) is one of the most frequent hospital-acquired infections occurring in intubated patients. Because VAP is associated with higher mortality, morbidity and healthcare costs, there is a need to solicit further research for effective preventive measures. VAP has been proposed as an indicator of quality of care. Clinical diagnosis has been criticized to have poor accuracy and reliability. Thus, the Centers for Disease Control and Prevention has introduced a new definition based upon objective and recordable data. The principal determinant of VAP development is the presence of the endotracheal tube (ETT). Contaminated oropharyngeal secretions pool over the ETT cuff and subsequently leak down to the lungs through a hydrostatic gradient. Lastly, biofilm develops on the inner ETT surface and acts as a reservoir for microorganism inoculum to the lungs. New preventive strategies are focused on the improvement of secretions drainage and prevention of bacterial colonization. The influence of gravity on mucus flow and body positioning can facilitate the clearance of distal airways, with decreased colonization of the respiratory tract. A different approach proposes ETT modifications to limit the leakage of oropharyngeal secretions.